VIDEO PLENARY 1: VID-LUM-02: Endoscopic ultrasound-guided cyanoacrylate glue injection for treatment of ano-urethral fistula - Jindal, Saurabh (Endosc Ultrasound, 2017)
BACKGROUND: Perianal fistulas are a frequent cause of morbidity and occur due to cryptoglandular infection, Crohn’s disease, radiotherapy, and malignancy. Perianal fistula occurring as a complication of anal canal surgery is an infrequent cause. We report endoscopic ultrasound (EUS)-guided management of a case of postsurgical perianal fistula with cyanoacrylate glue injection. CASE REPORT: A 35-year-old man presented with recurrent urinary tract infection requiring multiple courses of antibiotics for the past 15 years. He was operated for imperforate anus at birth and developed anal stricture requiring repeated bougienage dilation till 4 years of age. After anal dilatation, he had intermittent passing of urine through anal opening and was diagnosed to have ano-urethral fistula. He underwent multiple surgeries (three times) for the repair of fistula till the age of 16 and remained well till the age of 33. He presented with recurrent urinary tract infection. Radial EUS showed a tortuous fistula in anal canal communicating with prostatic urethra which was visualized due to air bubbles. A linear EUS-guided glue injection was planned. The patient was catheterized. Glue was injected into the middle part of fistula with successful closure. While injecting glue, the Foley’s catheter was rotated to avoid sticking of glue to the catheter. The patient is symptom-free on follow-up for 1 year. To conclude, we can say that EUS-guided cyanoacrylate glue can be safely attempted to treat postsurgical ano-urethal fistula.